A retrospective cohort study of survival in patients with healthcare-associated infection caused by Klebsiella pneumoniae – clinical, phenotypic, and genotypic predictors in a tertiary healthcare institution in Serbia (2022–2023) - Simonović, Marko; Rakonjac, Bojan; Nikolić, Aleksandra; Dabić, Jelena; Maksimović, Duško; Djurić, Momčilo; Taušan, Djordje; Šuljagić, Vesna (Vojnosanitetski pregled, 2026)
Background/Aim. Klebsiella (K.) pneumoniae is a frequent cause of healthcare-associated infections (HAI), particularly in intensive care units. Carbapenem-resistant strains represent a serious threat due to high mortality and limited therapeutic options. The aim of this study was to identify clinical predictors of 30-day mortality and to determine the presence of carbapenemase genes among K. pneumoniae isolates. Methods. A retrospective cohort study was conducted at the Military Medical Academy in Belgrade, Serbia. It included 121 patients with HAI caused by K. pneumoniae between January 2022 and December 2023. Clinical data were collected through active HAI surveillance. Isolation and antimicrobial susceptibility testing were performed according to standard microbiological procedures, and detection of carbapenemase genes was carried out using multiplex polymerase chain reaction. Survival was analyzed using the Kaplan-Meier method, and predictors of mortality were assessed using Cox regression analysis. Results. Thirty-day mortality was 59.5%. High resistance rates were observed to aminoglycosides (84.3%), fluoroquinolones (94.2%), and carbapenems (95.9%), while 67.8% of isolates were multidrug-resistant. The most common gene was blaOXA-48-like (45.5% in 2022 and 65.9% in 2023), followed by blaNDM (22.7% in 2022 and 4.5% in 2023), while blaKPC was detected only in isolates from 2023 (23.9%). The most frequently detected combination of carbapenemase genes was blaNDM + blaOXA-48-like (31.8% in 2022 and 5.7% in 2023). Detected genes had no significant effect on survival. Age ≥ 70 years, bloodstream infection, and intensive care units stay were identified as independent predictors of 30-day mortality. Conclusion. The high mortality among patients with HAI caused by carbapenem-resistant K. pneumoniae strains was primarily associated with patient characteristics and disease severity rather than the presence of specific carbapenemase genes.